2018
DOI: 10.1038/s41598-018-21598-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes induced by abiotic stresses in Artemisia annua

Abstract: Artemisia annua is known to be the source of artemisinin worldwide which is an antimalarial compound but is synthesised in very limited amount in the plant. Most research laid emphasis on the methods of enhancing artemisinin but our study has been planned in a way that it may simultaneously address two problems encountered by the plant. Firstly, to know the effect on the artemisinin content in the era of climate change because the secondary metabolites tend to increase under stress. Secondly, to identify some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Many of the genes are known to have responded to stimulus ( figure 3 ). Similar root waterlogging experiments in poplar, cotton and Artemisia annua [ 1 , 9 , 47 ] have shown increased expression of glycolysis, fermentation and some catabolism pathways, and decreased expression of synthesis pathways, cell wall and secondary metabolism-associated genes. The gene transcription responses to waterlogging in grapevine resemble that in Arabidopsis subjected to O 2 deprivation [ 7 ], indicating that the major factor in waterlogging stress is lack of O 2 , at least initially.…”
Section: Discussionmentioning
confidence: 81%
“…Many of the genes are known to have responded to stimulus ( figure 3 ). Similar root waterlogging experiments in poplar, cotton and Artemisia annua [ 1 , 9 , 47 ] have shown increased expression of glycolysis, fermentation and some catabolism pathways, and decreased expression of synthesis pathways, cell wall and secondary metabolism-associated genes. The gene transcription responses to waterlogging in grapevine resemble that in Arabidopsis subjected to O 2 deprivation [ 7 ], indicating that the major factor in waterlogging stress is lack of O 2 , at least initially.…”
Section: Discussionmentioning
confidence: 81%
“…Salinity also has an impact on artemisinin production. Vashisth et al (2018) reported a 14.68% increase in artemisinin content in A. annua plants under salt stress. They suggested that dihydroartemisinic acid acts as a free radical scavenger, helping to quench increased singlet oxygen, resulting in enhancement of artemisinin as the stable end product (Yang et al 2010).…”
Section: Stress Signal Interventionsmentioning
confidence: 98%
“…Leaf samples from the whole plant were collected and pooled for sequencing in triplicates as well as other molecular and metabolite analysis. Samples were stored in RNA later (Sigma Aldrich) at -800C until use [27].…”
Section: Methodsmentioning
confidence: 99%